2015
DOI: 10.3892/etm.2015.2531
|View full text |Cite|
|
Sign up to set email alerts
|

Paraptosis triggers mitochondrial pathway-mediated apoptosis in Alzheimer's disease

Abstract: Abstract. In previous years, increasing evidence has indicated that paraptosis and mitochondrial-mediated apoptosis may be associated with Alzheimer's disease (AD). However, the association between paraptosis and mitochondrial-mediated apoptosis, and the pathological processes underlying AD, remain elusive. In the present study, the β-amyloid precursor protein gene, and the gene mutations PS1M146L and L286V, were transfected to an SH-SY5Y cell line to establish an AD cell model. Subsequently, an MTT assay was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…107 In Alzheimer's disease, a previous study found that paraptosis was demonstrated in the early pathological stages of Alzheimer's disease, which might do harm to the mitochondria and lead to mitochondrial pathway-mediated apoptosis, subsequently. 108 Furthermore, activated microglia can cause neuronal cell death with characteristic vacuolation following blocking the caspase cascade. 109 Microglia are known as a key component of the protective scar that forms after SCI, so in-depth study on the role of activated microglia in paraptosis should be an interesting new direction.…”
Section: The Role Of Par Ap Tos Is and Pyrop Tos Is In S Pinal Cordmentioning
confidence: 99%
“…107 In Alzheimer's disease, a previous study found that paraptosis was demonstrated in the early pathological stages of Alzheimer's disease, which might do harm to the mitochondria and lead to mitochondrial pathway-mediated apoptosis, subsequently. 108 Furthermore, activated microglia can cause neuronal cell death with characteristic vacuolation following blocking the caspase cascade. 109 Microglia are known as a key component of the protective scar that forms after SCI, so in-depth study on the role of activated microglia in paraptosis should be an interesting new direction.…”
Section: The Role Of Par Ap Tos Is and Pyrop Tos Is In S Pinal Cordmentioning
confidence: 99%
“…Moreover, paraptosis is an independent caspases mechanism that displays mitochondrial swelling and produces cytoplasmatic vacuolation mainly derived from endoplasmic reticulum [39,40] . Despite several of these characteristics are in agreement with our observations, we identified cellular blebbing and apoptotic bodies in microscopy evaluation (black arrows in Figures S20 and S21) as well as annexin V labelling in flow cytometry analysis at 48 h of treatment but not at 24 h. Similarly, a study with an Alzheimer's disease cell model showed the presence of paraptotic cells at 24 h and with an increase in culture time, the presence of apoptotic cells after 48 h. In addition, a decrease in the expression levels of Bcl‐2 and Bax overexpression was observed at 48 and 72 h, suggesting that paraptosis finally unleashes mitochondrial apoptotic pathway [41] . Therefore, in the present case, it can be concluded that complexes 1 and 4 mediate paraptosis with subsequent apoptotic cell death.…”
Section: Resultsmentioning
confidence: 90%
“…In particular, diseases that belong to hereditary or age-related mitopathies have been demonstrated to be characterized by aberrant mitochondrial homeostasis and the consequent loss of control over cellular energy turnover (e.g., Alzheimer’s and Parkinson´s diseases, diabetes mellitus type 2, schizophrenia). Furthermore, these diseases are often associated with Mg deficiency 36 37 38 39 40 41 42 . To date, the mitochondrial Mg 2+ channel Mrs2 is the only transport mechanism that might link Mg deficiency with disturbed mitochondrial homeostasis 43 .…”
Section: Discussionmentioning
confidence: 99%